Understanding Sustainable Workforce Housing: Creating a Local Needs Assessment - Jeffrey P. Gellermann; Karla Lenfesty; Mark A. Brennan (EDIS, 2007)
FCS3258, a 5-page fact sheet by J. P. Gellermann, Karla Lenfesty, and M. A. Brennan, discusses the growing need for affordable housing in many areas of Florida and explains how readers can go about conducting a needs assessment to evaluate the demand for affordable/workforce housing in their areas. Published by the UF Department of Family Youth and Community Sciences, July 2007.